Cell Densities in the Mouse Brain: A Systematic Review - Keller, Daniel; Erö, Csaba; Markram, Henry (Frontiers in Neuroanatomy, 2018)
The mouse brain is the most extensively studied brain of all species. We performed an exhaustive review of the literature to establish our current state of knowledge on cell numbers in mouse brain regions; arguably the most fundamental property to measure when attempting to understand a brain. We found that we know very little about how many cells are present in most brain regions and even less about cell-type specific densities. We also found that reported values are so irreproducible that it is not possible to claim any ground truth value for any measurement despite the vast number of anatomical studies over decades. This reality check suggests that we need a new approach to obtain this simplest data on the mouse brain.